Brown adipose tissue human biomarkers: Which one fits best? A narrative review. Issue 48 (2nd December 2022) - Alito, Angelo; Quartarone, Angelo; Leonardi, Giulia; Tisano, Adriana; Bruschetta, Antongiulio; Cucinotta, Francesca; Milardi, Demetrio; Portaro, Simona
Abstract : Adipose tissue (AT) is an endocrine metabolically dynamic active tissue that plays a central role in the systemic energy balance and metabolic regulation. Brown AT represents approximately 1% of adult human AT, with an energy-burning function that uses fat to create heat. Brown AT activity was measured using 18F-fluorodeoxyglucose positron emission tomography/computed tomography. It has been shown that cold exposure could promote brown AT activation. However, many factors, such as aging and body mass index, may interfere with this activity. Many authors have discussed the role of factors specifically secreted by the AT in response to cold exposure. The aim of this review is to properly understand the effects of cold on AT and biomarkers and their possible application in rehabilitation medicine. A comprehensive literature review was performed to identify published studies regarding biomarkers of cold effects on Brown AT searching the following databases: PubMed, Science Direct, and Web of Science, from 2012 to 2022. After evaluation of the inclusion and exclusion criteria, 9 studies were included in this review. We reported the overall influence of cold exposure on brown AT activity, its related biomarkers, and metabolism, demonstrating that the therapeutic role of cold exposure needs to be better standardized. From our data, it is important to design proper clinical trials because most cold applied protocols lack a common and homogeneous methodology.